The novel of A. Bely «Petersburg» in the context of foreign modernism (Eurasian Journal of Philology Science and Education, 2019)
Andrei Bely’s novel «Petersburg» is in the context of the development of Western literature. Thepoetics of Andrei Bely and Joyce’s novels is based on the reduction of anthropological characteristics ofliterary characters.Both writers actively use grotesque, irony and parody. These sources of comic effect contribute tothe reduction of anthropological poetics characteristic of realistic literature. Satirical art techniques basedon the concentration and synthesis of human characteristics (the grotesque), on the game of meaning(irony and parody). In addition, a significant part of satirical techniques distorts, even schematizes theappearance of a person.In the novel «Ulysses» Joyce draws broken images of characters, expands the artistic world, includingspatial images and cultural context. This brings together the creative method of Joyce with the poeticsof Andrei Bely, whose novel «Petersburg» presents laconic portraits of characters that have turned intoshadows, global images of Russia, Petersburg, East and West, playing a significant role in the work.It is also obvious that Proust and Andrei Bely updated the genre of the novel on similar principles.The writers’ consistent interest in the past, the high status of ontological images in their novels, the singlestream of the past and the present, the reduced anthropological properties of the characters – that’s whatbrings together the novels of Proust and Andrei Bely.